Bioactive proteins in breast milk and their impact on infant gut development - Hermawati, Luluk; Irawati, Nur Bebi Ulfah; Zulfa, Hilizza Awalina; Fidusia, Amanah Eva; Agustianti, Erika; Husna, Firda Asma’ul (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: During early stages of life, breast milk is the mainstay of nutrition. Beyond delivering vital amino acids, certain proteins like lactoferrin, α-lactalbumin, sIgA, and lysozyme bolster the infant's gastrointestinal system and provide protective mucosal factors alongside immunomodulatory functions, helping shape the gut microbiome. The goal of this review is to analyze the scientific literature on the types and composition of proteins in breast milk, their biological functions, and their effects regarding the development and protection of the infant’s gastrointestinal tract with special focus on the mechanisms of mucosal immunity, mucosal defense, and microbial colonization. Methods: A literature search was conducted through PubMed, and Google Scholar databases with the terms bioactive, breastmilk, gut, infant, and microbiota. Only articles published between 2015 and 2025 were chosen for their relevance to the topic and methodological soundness. Findings: Whey proteins, which dominate the early lactation phase, contain bioactive peptides that are easily absorbed and support enterocyte maturation. Lactoferrin and sIgA contribute to maintaining mucosal integrity and preventing pathogen colonization. Growth factors such as epidermal growth factor (EGF) and transforming growth factor-beta (TGF-β) accelerate epithelial maturation and strengthen tight junctions, while other proteins like osteopontin and beta-casein help shape a favorable microbial ecosystem. Conclusion: Breast milk proteins contribute multifaceted roles in gastrointestinal and immune system development, underscoring the importance of exclusive breastfeeding as a foundation for neonatal gastrointestinal and immunological health. Novelty/Originality of this article: This review provides a comprehensive synthesis of the diverse roles of breast milk proteins in shaping infant gastrointestinal development and mucosal immunity by emphasizing perspectives that integrate evidence focused on nutrition, immunology, and the microbiome in a way that has not been fully addressed in previous literature.